An Interior Point Method for Linear Programming (Journal of Computational Mathematics, 2021)
In this paper we present an interior point method which solves a linear programming problem by using an affine transformation. We prove under certain assumptions that the algorithm converges to an optimal solution even if the dual problem is degenerate as long as the prime is bounded, or to a ray direction if the optimal value of the objective function is unbounded.